Interaction between a coating-borne peptide of the Brassica pollen grain and stigmatic S (self-incompatibility)-locus-specific glycoproteins. - Doughty, J (1993)
Methods are described for the removal of the sporophytic pollen grain coating of Brassica oleracea and for the isolation of coat polypeptides. The coat contains a small number of proteins ranging from 6 to 45 kDa. Many of the larger proteins are glycosylated, while all carry high positive charges resulting in pI values from 8.5 to 11. Polypeptides with pI values of 9.5, 9.0, and 8.5 possess strong esterase activity. No major differences could be detected in either pI values or molecular masses of pollen-coating polypeptides from grains carrying different sporophytically expressed S (self-incompatibility) alleles. Mixing pollen coat proteins with stigmatic extracts results in a conspicuous binding interaction involving female S-locus-specific and perhaps S-locus-related glycoproteins. This interaction, which is reversed by heating in the presence of SDS, results in an apparent charge shift of the female glycoprotein(s) of up to 2 pI units. The male participant in this interaction has been isolated by using a combination of fast protein liquid chromatography and reverse-phase HPLC and was shown to be a 7-kDa nonglycosylated peptide. Experiments with whole pollen cultured in vitro show challenge with stigmatic extracts to stimulate the release of gametophytic and sporophytic polypeptides and to result in the formation of a conspicuous interaction product, demonstrating the 7-kDa peptide to be freely available within the coating of pollen in vivo.